Investigating Online Mis- and Disinformation in Cyprus: Trends and Challenges - Dimitrios Giomelakis; Costas Constandinides; Maria Noti; Theodora A. Maniou (Journalism and Media)
Information disorder constitutes a critical threat to the public sphere, posing significant challenges and negatively affecting society, public trust, and overall democratic stability. This article investigates the phenomenon of online mis- and disinformation in Cyprus, drawing on people’s perceptions of this topic as well as the characteristics that enable disinformation campaigns to go viral. The study explores news consumption habits, people’s concerns about the impact of online disinformation, exposure to false or misleading content, common sources, verification methods, and media literacy. Furthermore, the study aims to shed light on the phenomenon of online mis- and disinformation in Cyprus and identify users’ perspectives.